Implementasi Kriptografi dengan Metode Caesar Cipher untuk Mengamankan Data File di Javanetbeans - haryanzelina bancin; mira aripin panjaitan; sabrina putri; Adnan Buyung Nasution (CV. ITTC INDONESIA, 2023)
The rapid development of information and telecommunications technology makes it easier for us to carry out activities in the form of confidential files or data, therefore data security is needed to secure confidential files. This research was conducted to implement Caesar cipher cryptography. Where Cryptography can only be carried out by certain people who understand its use so that Cryptography can be categorized as a safe place to store confidential data. This system uses the caesar cipher algorithm which is processed with the Java NetBeans program to produce ciphertext. Where files that can be encrypted are text document files with the .txt extension. txt data is a Domain Name Service (DNS) data type that contains text information sources for sources within the domain, by adding to the domain a file with the .txt extension can be used for various important purposes. The result of this research is a cryptographic implementation of the Caesar cipher method to secure data files in Javanetbeans. So it can be concluded that data security using the Caesar Cipher method is proven to work on Java Netbeans.